Montreal cognitive assessment (MoCA): Normative data for old and very old Czech adults. Issue 1 (2nd January 2017) - Kopecek, Miloslav; Stepankova, Hana; Lukavsky, Jiri; Ripova, Daniela; Nikolai, Tomas; Bezdicek, Ondrej
ABSTRACT: The principal aim of our study was to present norms for old and very old Czech adults on the Czech version of the Montreal Cognitive Assessment (MoCA) and investigate the influence of social and demographic factors on MoCA performance. We analyzed 540 adults aged ≥ 60 years (5-year age categories; nationally representative sample in terms of sex and educational level), who met strict inclusion criteria for the absence of neurodegenerative disorders and performed within normal range in neuropsychological assessment. Using multiple regression model, we found that MoCA performance was affected by age and education (both p  < .001) but not sex. The study provides normed percentile estimates for MoCA performance stratified by age (60–74 years; ≥ 75 years) and education lower versus higher. We also present percentile equivalents for the MoCA and Mini-Mental State Examination (MMSE) for use in clinical practice. We found age- and education-related effects on MoCA performance which support the use of culturally adapted normative data.